2017
DOI: 10.1093/jpepsy/jsx147
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Evaluating Smartphone-Based Virtual Reality to Improve Chinese Schoolchildren’s Pedestrian Safety: A Nonrandomized Trial

Abstract: Pedestrian safety training via smartphone-based VR provides children the repeated practice needed to learn the complex skills required to cross streets safely, and also helps them improve self-efficacy to cross streets. Given rapid motorization and global smartphone penetration, plus epidemiological findings that about 75,000 children die annually worldwide in pedestrian crashes, smartphone-based VR could supplement existing policy and prevention efforts to improve global child pedestrian safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Compared to K‐12 settings, higher education has experienced more extensive usage of VR technologies, especially in the fields of engineering and health and medicine. Engineering is a subject only offered in higher education curricula, and more topics are covered in health and medicine at university level than at K‐12 level; the latter mainly focuses on safety education, for example, pedestrian safety (McComas et al, 2002; Schwebel et al, 2018; Thomson et al, 2005), fire safety (Çakiroğlua & Gökoğlub, 2019; Padgett et al, 2006), and life skill development (Vogel et al, 2004). Furthermore, within the K‐12 context, VR‐based instruction was more commonly seen in elementary schools than middle or high schools, indicating educational researchers' keenness to explore its potential among younger students, particularly in the subjects of social science and safety education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to K‐12 settings, higher education has experienced more extensive usage of VR technologies, especially in the fields of engineering and health and medicine. Engineering is a subject only offered in higher education curricula, and more topics are covered in health and medicine at university level than at K‐12 level; the latter mainly focuses on safety education, for example, pedestrian safety (McComas et al, 2002; Schwebel et al, 2018; Thomson et al, 2005), fire safety (Çakiroğlua & Gökoğlub, 2019; Padgett et al, 2006), and life skill development (Vogel et al, 2004). Furthermore, within the K‐12 context, VR‐based instruction was more commonly seen in elementary schools than middle or high schools, indicating educational researchers' keenness to explore its potential among younger students, particularly in the subjects of social science and safety education.…”
Section: Resultsmentioning
confidence: 99%
“…With projectors being replaced by organic light‐emitting diode (OLED) display panels in HMDs, the percentage of projector‐based VR showed a sharp decline in the literature (from 19% to 5%). Moreover, although no drastic changes were found in the percentage of studies on VR glasses, references to them changed over time from polarised 3D glasses (Kim, 2006; Smith et al, 2007) to mobile‐based VR viewers such as Google Cardboard and Gear VR (Moro et al, 2017; Schwebel et al, 2018; Xie et al, 2019). In addition, accessories such as joysticks, motion capture devices, and haptic gloves have seen increased usage in education as peripheral VR equipment in the last decade.…”
Section: Resultsmentioning
confidence: 99%
“…VR applications are used in many areas. In addition to pain and anxiety, VR has been used for the pharmacological stroke prevention and to teach patients about the results of atrial fibrillation (Balsam et al, 2018), stroke rehabilitation (Laver, George, Thomas, Deutsch, & Crotty, 2015), improving the skills for performing surgery (Piromchai, Avery, Laopaiboon, Kennedy, & O'Leary, 2015), nasogastric tube placement (Choi, 2017), nursing education (Farra, Smith, & Ulrich, 2017) and school children's pedestrian safety (Schwebel et al, 2018). VR can be used safely in the health care and education areas, and it is a useful application in reducing pain, fear and anxiety-particularly in children during invasive procedures and for increasing the success of procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The second issue is the lack of systematic comparison of knowledge and behavioral learning outcomes in IVR. For example, Taranilla et al (2019) used test questions to measure the degree to which knowledge was mastered by students [8], and Schwebel et al (2018) tested the effect of IVR on improving children's pedestrian performance by coding their street-crossing behaviors. Although the research results showed that learners improved their level of knowledge or behavioral performance, there was a lack of comparison in terms of the degree of improvement between the two [30].…”
Section: Knowledge and Behavioral Learningmentioning
confidence: 99%